Spatiotemporal dynamics of red blood cells in capillaries in layer I of the cerebral cortex and changes in arterial diameter during cortical spreading depression and response to hypercapnia in anesthetized mice. (2nd June 2019) - Unekawa, Miyuki; Tomita, Yutaka; Toriumi, Haruki; Osada, Takashi; Masamoto, Kazuto; Kawaguchi, Hiroshi; Izawa, Yoshikane; Itoh, Yoshiaki; Kanno, Iwao; Suzuki, Norihiro; Nakahara, Jin
Abstract: Objective: Control of red blood cell velocity in capillaries is essential to meet local neuronal metabolic requirements, although changes of capillary diameter are limited. To further understand the microcirculatory response during cortical spreading depression, we analyzed the spatiotemporal changes of red blood cell velocity in intraparenchymal capillaries. Methods: In urethane‐anesthetized Tie2‐green fluorescent protein transgenic mice, the velocity of fluorescence‐labeled red blood cells flowing in capillaries in layer I of the cerebral cortex was automatically measured with our Matlab domain software (KEIO‐IS2) in sequential images obtained with a high‐speed camera laser‐scanning confocal fluorescence microscope system. Results: Cortical spreading depression repeatedly increased the red blood cell velocity prior to arterial constriction/dilation. During the first cortical spreading depression, red blood cell velocity significantly decreased, and sluggishly moving or retrograde‐moving red blood cells were observed, concomitantly with marked arterial constriction. The velocity subsequently returned to around the basal level, while oligemia after cortical spreading depression with slight vasoconstriction remained. After several passages of cortical spreading depression, hypercapnia‐induced increase of red blood cell velocity, regional cerebral blood flow and arterial diameter were all significantly reduced, and the correlations among them became extremely weak. Conclusions: Taken together with our previous findings, these simultaneous measurements of red blood cell velocity in multiple capillaries, arterial diameter and regional cerebral blood flow support the idea that red blood cell flow might be altered independently, at least in part, from arterial regulation, that neuro‐capillary coupling plays a role in rapidly meeting local neural demand.